2017
DOI: 10.3928/24748307-20170503-01
|View full text |Cite
|
Sign up to set email alerts
|

Prioritized Health Literacy and Clear Communication Practices For Health Care Professionals

Abstract: Background: Health care professionals need more and better training about health literacy and clear communication to provide optimal care to populations with low health literacy. A large number of health literacy and clear communication practices have been identified in the literature, but health professions educators, administrators, and policymakers have lacked guidance regarding which practices should be prioritized among members of the health care workforce. Objective: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
81
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(84 citation statements)
references
References 26 publications
1
81
0
2
Order By: Relevance
“…Teach Back is a health communication strategy used to confirm patient understanding in a non-shaming way. Teach Back is among the most important skills health care workers (HCWs) need for effective communication with patients (Coleman, Hudson, & Pederson, 2017). The goal for this project was to train HCWs in the use of Teach Back, using a standardized operational definition, which transforms Teach Back into a set of skills that are easy to learn, verifiable in practice, and, potentially, measurable in research.…”
mentioning
confidence: 99%
“…Teach Back is a health communication strategy used to confirm patient understanding in a non-shaming way. Teach Back is among the most important skills health care workers (HCWs) need for effective communication with patients (Coleman, Hudson, & Pederson, 2017). The goal for this project was to train HCWs in the use of Teach Back, using a standardized operational definition, which transforms Teach Back into a set of skills that are easy to learn, verifiable in practice, and, potentially, measurable in research.…”
mentioning
confidence: 99%
“…Coleman, Hudson et Maine [19] définissent la compétence en littératie en santé des professionnels comme les savoirs, savoir-faire et attitudes dont les professionnels de la santé ont besoin pour mener une action efficace au regard de l'information et des services à donner à une patientèle de faible niveau de littératie. Ces compétences renvoient à de bonnes pratiques en matière de littératie en santé, qui visent entre autres à adopter une approche de précaution dans toutes les communications en santé, et ce, dans un style clair et simple [20,21].…”
Section: Littératie Et Professionnels De La Santéunclassified
“…En fait, les « bonnes pratiques » en littératie en santé recensées dans les écrits [18][19][20][21][22][23][24] peuvent être regroupées autour de quatre composantes ( Figure 1 ). Toutefois, malgré ce cadre, plusieurs questions subsistent quant à la compréhension des dimensions de la compétence en matière de littératie des professionnels ainsi qu'à la façon d'en favoriser le développement [3,19].…”
Section: Littératie Et Professionnels De La Santéunclassified
“…This is especially problematic for people with a lower health literacy with whom health professionals report feeling unprepared to communicate . Consequently, several experts have proposed clear communication and health literacy curricula for health professionals in the United States and Europe . Training in these competencies has shown the potential to improve communication skills in the short term, but it has been suggested that training would have to be ongoing, as improvements were not sustained …”
Section: Introductionmentioning
confidence: 99%